PENINGKATAN CALISTUNG (MEMBACA, MENULIS, BERHITUNG) MELALUI TAMAN DOLANAN LITERASI DAN NUMERASI - Endang Widati; Marlina, Eva; Harminto, Yopi; Triyono (Jurnal Jaringan Penelitian Pengembangan Penerapan Inovasi Pendidikan (Jarlitbang), 2025)
To enhance students' literacy and numeracy skills, SDN 1 Ngancar implemented the "Taman Dolanan Literasi dan Numerasi". This program comprises a Literacy Garden ("Lumbung Basa") and a Numeracy Playground. The aim of the "Taman Dolanan Literasi dan Numerasi" is to provide an innovative approach to improving children's basic literacy and numeracy skills at SDN 1 Ngancar. The "Lumbung Basa" Literacy Garden emphasizes the use of the Javanese language in students' daily lives, while the Numeracy Playground is an educational tool based on traditional games combined with fun literacy and numeracy activities. A qualitative approach was used to assess the program's effectiveness. This approach was chosen to determine the effectiveness of the "Taman Dolanan Literasi dan Numerasi" in improving students' literacy and numeracy skills through traditional games, encompassing planning, implementation, observation, and reflection.  Research results indicate an improvement in children's reading, writing, and numeracy skills after participating in the "Taman Dolanan Literasi dan Numerasi" program. Children demonstrated increased learning motivation, critical thinking skills, and collaborative skills through various traditional games such as congklak, engklek, and dakon. The implementation of this playground also successfully created an interactive and contextual learning environment, enabling children to understand basic literacy and numeracy concepts more meaningfully.  It not only supports cognitive development but also provides learning experiences relevant to local culture.